Karakterisasi Konsumsi Energi Motor Bldc terhadap Beban Dinamis pada Kendaraan Listrik Hibrida - Wijaya Putra; Supa Kusuma Aji; Septyana Riskitasari; Ahmad Hanif Firdaus (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rapid growth of motor vehicles, exceeding 169 million units in Indonesia by 2025, highlights the urgent need for energy-efficient and environmentally friendly transportation solutions, such as hybrid vehicles. Brushless Direct Current (BLDC) motors are crucial components in these systems due to their high efficiency and compact design, particularly when directly integrated into wheels. This study specifically aims to analyze the impact of varying loads on the power consumption of a BLDC motor within a front-wheel-drive hybrid motorcycle prototype equipped with a Continuously Variable Transmission (CVT) system. Experimental data was collected using a wattmeter on a prototype subjected to different passenger loads: 55 kg, 75 kg, and 100 kg, at constant speeds of 20 and 40 km/h. The findings consistently show that an increase in load significantly and positively correlates with higher power consumption of the BLDC motor. For instance, at 40 km/h, power consumption for a 100 kg load reached 729.578 Watt, whereas for a 55 kg load it was 649.605 Watt. This demonstrates that greater effort (power) is required from the motor to overcome the inertia and increased resistance associated with heavier loads. These results contribute to optimizing energy efficiency in hybrid vehicle design and underscore the importance of load management for sustainable transportation.